JARINGAN PERTEMANAN MAHASISWA BATAK DI LINGKUNGAN UNIVERSITAS RIAU (Studi Kasus Adaptasi Sosial Mahasiswa Batak Toba, Karo dan Mandailing) - Geral Andika Panjaitan; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the University of Riau with the formulation of problems (1) How the Batak Student Friendship Network in the University of Riau (Case Study of Social Adaptation of Batak Toba, Karo and Mandailing Students), (2) Factors that influence the network of friends of Batak students in the environment Riau University. The purpose of this study was to describe the Batak Student Friendship Network in the University of Riau (Case Study of Social Adaptation for Batak Toba, Karo and Mandailing Students) and to describe the factors that influence the Batak Student Friendship Network in the University of Riau. This research is a qualitative descriptive study. , the subjects in this study were Batak students (Toba, Karo and Manailing) at the University of Riau. To collect data in this study, researchers used interview guidelines and questionnaires. The results of this study indicate that the Toba and Karo Batak students are more likely to choose to be friends with their fellow ethnic groups and form less friendship with the Mandailing Batak ethnic students, and vice versa with the Mandailing Batak students who prefer to be friends with students outside the Batak ethnic group itself rather than their peers. Batak ethnicity. There are religious factors and stereotypes that are influencing factors in the network of friends among Batak students (Toba, Karo and Mandailing) in the University of Riau. Keywords: Network of Friends, Adaptation of Batak Students